Pengaruh Harga, Kualitas Pelayanan dan Lokasi pada Laguna Family Karaoke di Sungai Penuh - Edia Satria (J-MAS (Jurnal Manajemen dan Sains), 2020)
This research was conducted to find out (1) The effect of Prices on Customer Satisfaction at Laguna Family Karaoke In Sungai Penuh. (2) The influence of Service Quality on Customer Satisfaction at Laguna Family Karaoke In Sungai Penuh. (3) The influence on customer Satisfaction at Laguna Family Karaoke In Sungai Penuh. (4) The influence of Price, Service Quality and Location simultaneously on Customer Satisfaction at Laguna Family Karaoke In Sungai Penuh. This research is quantitative research. The population in this research is consumers at Laguna Family Karaoke in 2019. The sampling technique used in this research was accidental sampling. The sample in this research was 80 consumers in Laguna Family Karaoke. Data collection techniques using a questionnaire. Validity test using value corrected item total correlation. Reliability test using alpha cronbach. Data analysis technique use multiple linear regression tests. Research result show that : (1) there is a positive influence between price and customer satisfaction at Laguna Family Karaoke In Sungai penuh this is proven from t hitung > dari t tabel which one 7,456 >  2,021 and significant 0,000 < 0,05. (2) There is no positive influence between service quality on customer satisfaction at Laguna Family Karaoke In Sungai Penuh this is proven from t hitung< dari t tabel which one -0,918 <2,021 and significant 0,363 > 0,05. (3) there is a positive influence between location and customer satisfaction at Laguna Family Karaoke In Sungai Penuh this is proven from t hitung < dari t tabel which one -2,371 > 2,021 and significant 0,020 < 0,05. (4) there is a positive influence between prices, service quality and location to customer satisfaction at Laguna Family Karaoke In Sungai Penuh this is proven from oleh fhitung  > ftabel that is 24,686> 2,58  dan signifikan 0,000 < 0,05.